Differences in Levels of Social Anxiety in Adolescent Girls in Makassar City Seen from Locus of Control - Damayanti, Risa; Hamid, Harlina; Ismail, Ismalandari (Polteknik Ilmu Pemasyarakatan, 2023)
One of the developmental tasks that adolescents must go through is social adjustment in adolescents. Difficulties in the social adjustment process due to the standards that apply in the environment make teenagers afraid of being evaluated negatively and even experiencing social anxiety. One factor of anxiety is the role of the control center or locus of control. Locus of control is divided into internal and external. The aim of this research is to see whether there are differences in the level of social anxiety in adolescent girls in terms of locus of control. The criteria for subjects in this research are female teenagers aged 12-18 years who live in Makassar City. The subjects in this research were 400 female teenagers who live in Makassar City. The method used in this research is quantitative. Data were analyzed using the Mann-Whitney U Test. The results showed that there were differences in the level of social anxiety among female adolescents in the city of Makassar in terms of Locus of Control with a significance value of 0.000 (p<0.05). This research illustrates that adolescents with an external locus of control orientation tend to have high social anxiety. It is hoped that the results of this research will be able to pay attention to what things adolescent girls can control when facing social situations or in the social environment. Teenagers are expected to have understanding and confidence and also be able to see things that are beyond their personal abilities, which are things that can have an impact on themselves.